Provincial Comparisons in the Canadian Incidence Study of Reported Child Abuse and Neglect - 2008: Context for Variation in Findings - Fallon, Barbara; Trocme, Nico; MacLaurin, Bruce; Sinha, Vandha; Helie, Sonia (International Network of Child and Adolescent Resilience, 2015)
Objectives: This paper compares findings of five provincial incidence studies (British Columbia, Alberta, Saskatchewan, Ontario and Quebec) in order to investigate and explain variations in provincial findings with the hope of promoting future provincial comparisons. Methods: The provincial incidence study reports were produced as part of the larger CIS- 2008. The CIS-2008 is a third national study that captured information about children and their families reported for maltreatment by child protection services. Results: The findings compared rates per 1, 000 children. Some dimensions measured such as rates of substantiation and transfers to ongoing services and placement were similar across the provinces studied. Others, such as rates of maltreatment-related investigations, the classification of risk investigations, rates of substantiated neglect, emotional maltreatment and intimate partner violence differed more between the five provinces. Conclusions: Socio-demographic differences, differences in screening and investigation procedures, clinical case practice differences and methodological differences were presented as possible sources of variation in the data across provinces. The results, however, are not evaluative as they do not present data that examine outcomes for children and their families. Implications: While comparisons between provinces can now be made, further research on the impact of the differences in services to children and their families and the outcome of these services is still needed distinguishable from emotional resilience and dispositional traits. Empirical research on the nature of interpersonal resilience in challenged contexts is warranted. Intervention Social Sciences and Humanities Research Council of Canada Aid to Research Workshops and Conferences Grant, The Canadian Incidence Study of Reported Child Abuse and Neglect, 2008: Provincial / First Nations Research Network Workshop, File number 646- 2011-0130, Council Identification Number 126305